The Promise of Lung Organoids for Growth and Investigation of Pneumocystis Species - Tisdale-Macioce, Nikeya; Green, Jenna; Perl, Anne-Karina T.; Ashbaugh, Alan; Wiederhold, Nathan P.; Patterson, Thomas F.; Cushion, Melanie T. (Frontiers in Fungal Biology, 2021)
Pneumocystis species (spp.) are host-obligate fungal parasites that colonize and propagate almost exclusively in the alveolar lumen within the lungs of mammals where they can cause a lethal pneumonia. The emergence of this pneumonia in non-HIV infected persons caused by Pneumocystis jirovecii (PjP), illustrates the continued importance of and the need to understand its associated pathologies and to develop new therapies and preventative strategies. In the proposed life cycle, Pneumocystis spp. attach to alveolar type 1 epithelial cells (AEC1) and prevent gas exchange. This process among other mechanisms of Pneumocystis spp. pathogenesis is challenging to observe in real time due to the absence of a continuous ex vivo or in vitro culture system. The study presented here provides a proof-of-concept for the development of murine lung organoids that mimic the lung alveolar sacs expressing AEC1 and alveolar type 2 epithelial cells (AEC2). Use of these 3-dimensional organoids should facilitate studies of a multitude of unanswered questions and serve as an improved means to screen new anti- PjP agents.